Long-term follow-up after retrosternal ileocolic esophagoplasty in two cases of long-gap esophageal atresia: why it is still a valid option as a rescue strategy - Léonard, Matthieu; Deswysen, Yannick; Scheers, Isabelle; Thoma, Maximilien; de Magnée, Catherine; Stephenne, Xavier; Dumitriu, Dana; Menten, Renaud; Reding, Raymond; Tambucci, Roberto (Frontiers in Pediatrics, 2023)
Esophageal replacement surgery in children is sometimes necessary for long-gap esophageal atresia. Ileocolic esophagoplasty in the retrosternal space can serve as a good alternative technique in case of hostile posterior mediastinum. We present two cases of successful ileocolic transposition performed at 6 months of ageEsophageal replacement was performed through a midline laparotomy incision associated with a left cervical approach. The ileocolic transplant was pediculized on the right superior colic artery after ligation of the right colic and ileocolic vessels. Retrosternal tunnel was created and the ileocolic transplant pulled through it to reach the cervical region. Proximally, esophageal-ileal anastomosis and, distally, colonic -gastric anastomosis were performed. Ileocolic continuity was repaired.There were no early postoperative complications. In both cases, the patients presented oral feeding difficulties during the first 6 postoperative months. Thereafter, full oral feeding was achieved, and both patients were clinically asymptomatic during the following 18 and 20 years, respectively, with satisfactory oral radiological assessments, showing no redundancy or inappropriate growth of the graft, as well as no anastomotic stricture. Currently, these patients did not complain of dysphagia, pathological reflux, or respiratory symptoms.When native esophagus preservation in long-gap esophageal atresia is estimated unfeasible, ileocolic transposition in the retrosternal space might be considered as a good and safe option, particularly in those difficult cases after multiple previous surgical attempts and mediastinitis. This technique is putatively associated with a beneficial anti-reflux effect, thanks to the presence of the ileocecal valve, in preventing cervical peptic esophagitis. Long-term follow-up confirm that transposed colon in the retrosternal space did not suffered of any abnormal modification in size and growth.